DETERMINANTS OF SUBSIDIZED HOUSING DEMAND IN KARANGANYAR DISTRICT CENTRAL JAVA PROVINCE - Ismoyowati, Dewi (EP FEB UNS, 2017)
House is representing requirement of human being base besides food and clothing. In its growth in the reality house also represent interesting invesment alternative on the chance of capital gain in the future. Area housing of subsidiy of Karanganyar region represent one of the correct choice alternative to cultivation of invesment in housing area, either from price facet, facility, freshment, location which located in Karanganyar region can fulfill requirement of modern society of house besides for residence also for habitable.. This research has aim to to analyse factors which influencing request of housing specially type of subsidy at Karanganyar region. Analysis for this research is using doubled linear regression. This Research responder is dweller of housing subsidy of Karanganyar region. Based on result of analysis indicate that price, locatio, substitution price and earnings have an effect on to decision of purchasing of house, whereas fasility and environment have not an effect on to decision of purchasing of house. Ttesting the coefficient of determination is known that 64.2 percent of the variation that occurs in the purchase decision variables jointly influenced by the perception variable price, amenities, location, environment, income and substitution rates. While the rest equal to 35,8 percent influenced by other factors. Based on the result of this research we got that subtitution price factor very having an effect on in purchasing of house. Seen from level of coefficient influencing decision of purchasing of subtitution price equal to 2,175; earnings equal to 2,100; location equal to 2,141; and price equal to 2,133